Back Cover. Issue 1 (21st December 2021) - Unknown
Abstract : Solar‐driven interfacial evaporation received extensive attention due to their potentials in water, energy and environmental sustainability. However, accumulation of salts are major challenges for solar desalination. Gan et. al. reported a self‐salt‐cleaning architecture to realize a maintenance‐free operation for hypersaline brines, paving the way towards zero‐liquid‐discharge treatment of hypersaline water from reverse osmosis systems, and accelerated salt mining for batteries. Abstract : Solar‐driven interfacial evaporation received extensive attention due to their potentials in water, energy and environmental sustainability. However, accumulation of salts are major challenges for solar desalination. Gan et. al. reported a self‐salt‐cleaning architecture to realize a maintenance‐free operation for hypersaline brines, paving the way towards zero‐liquid‐discharge treatment of hypersaline water from reverse osmosis systems, and accelerated salt mining for batteries.